Intersemiotic translation: Comments on audio description from a Translation Studies perspective - Jung, Linus; Chica Nuñez, Antonio Javier (Glottodidactica, 2018)
There is no doubt that Translation Studies have firmly established themselves as an independent scientific field. However, there are thematic overlaps in some areas concerning other disciplines. This work investigates the relations between interlinguistic translation and intersemiotic translation from the point of view of translation studies. First of all, a set of criteria for the identification of proper translation is offered and, in a second step, we examine how theoretical elements like communicative equivalence and communicative value can be transferred to a linguistic discourse by means of the intersemiotic translation modality known as audio description (AD).